Metabolomic Signature of Hypertension - Qureshi, Waqas Tariq (Wake Forest University, 2015)
Metabolomics is a comprehensive study of small molecular end products of metabolism (metabolites) in living organisms. These metabolites are directly modified by the metabolic processes that are governed by organism’s genome, environment and diet. With advancement in technology, a large number of metabolites can be measured in various body fluids. The changes in metabolome precede disease phenotypes and thus, provide the niche for use of metabolomics in early detection and prevention of diseases. Several lines of evidence suggest that hypertension is closely associated with metabolic diseases and derangements. This thesis work was aimed at literature review of current metabolomic studies of hypertension and identified a knowledge gap regarding metabolomic signature of prevalent and incident hypertension. This was addressed by performing a metabolomic analysis of multi-ethnic cohort of Insulin Resistance Atherosclerosis Study. The advanced techniques utilized for sampling, extraction, detection and analyzing a metabolome were also then reviewed. Understanding these metabolic perturbations in hypertension may lead to development of effective prevention strategies for hypertension which currently inflicts ~900 million people worldwide.
Keywords: Epidemiology; Hypertension; Magnetic resonance imaging spectroscopy; Mass spectrometry; Metabolomics